Penyembuhan Pranic Healing terhadap Kesehatan Tubuh Fisik Primigravida Trimester III - Cahyaning Puji Astuti; Melyana Nurul Widyawati (Jurnal Keperawatan Silampari, 2019)
This study aims to improve the physical health condition of third trimester primigravida pregnant women. The method in this study uses a randomized controlled trial design. This type of research uses pre-test & post-test group design. The results of this study indicate that the results of organ energy as an indicator of physical body health have increased the frequency of pre and post test. The repeated ANOVA test showed a decrease in both groups. While the Wilcoxon test results showed that there were differences in the post test 2 energy organs p = 0.013 (<0.05), post test 3 p value 0.001 (<0.05). Conclusion, pranic healing therapy can increase the physical energy of pregnant women. Keywords: Organ Energy, Trimester III Pregnancy, Pranic Healing, Primigravida